2012
DOI: 10.1007/s10067-012-1945-0
|View full text |Cite|
|
Sign up to set email alerts
|

Parameters related to a positive test result for FDG PET(/CT) for large vessel vasculitis: a multicenter retrospective study

Abstract: The purpose of this study was to identify clinical and laboratory parameters that may improve the effectiveness of the use of fluorodeoxyglucose positron emission tomography ((18)F-FDG PET)(/CT) for diagnosing large vessel vasculitis (LVV), and secondarily to assess the contribution of (18)F-FDG PET/CT in finding other diagnoses for patients without signs of LVV on the scan. A multicenter retrospective study of (18)F-FDG PET(/CT) scans performed between January 2000 and December 2009 for clinical suspicion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 54 publications
1
26
0
2
Order By: Relevance
“…Inflammation of unknown origin (IUO), without fever, and fever of unknown origin (FUO) may represent different clinical presentations of the same underlying disease [1]. This concept was supported in five recent studies [2]. These studies showed that the diagnostic yield, the distribution in categories of the underlying etiologies (i.e.…”
Section: Introductionmentioning
confidence: 93%
“…Inflammation of unknown origin (IUO), without fever, and fever of unknown origin (FUO) may represent different clinical presentations of the same underlying disease [1]. This concept was supported in five recent studies [2]. These studies showed that the diagnostic yield, the distribution in categories of the underlying etiologies (i.e.…”
Section: Introductionmentioning
confidence: 93%
“…As reported by Hooisma (2012), the diagnostic standard method for LVV, especially in giant cell arteritis (GCA), is a temporal artery biopsy, but the test results can be false negative in 15-70%, which may delay the diagnosis; in Takayasu's arteritis (TA), which affects the aorta and its main branches, as well as the coronary and pulmonary arteries, routine histological examination is not suitable. Besson and coworkers (2011) reported in their meta-analysis that diagnostic performance of FDG-PET in giant cell arteritis provided sensitivity and specificity of 80% and 89%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Ergul (2011) and Hooisma (2012) highlighted the utility of PET in early diagnosis of LVV and in discovery of occult inflammatory or neoplastic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Ethnicity is an important risk factor for GCA, with the highest incidence found among people of Scandinavian origin (6). GCA is rare in people of Asian descent, and to date only a few cases have been reported in South Korea (7)(8)(9)(10). In contrast, TA seems to be more prevalent in Asian countries compared to Western countries.…”
Section: To the Editormentioning
confidence: 95%
“…Third, large vessel involvement in GCA may occur without involvement of the temporal arteries. In a recent series it was found that half of patients with increased 18 F-FDG uptake in the thoracic aorta and its main branches, which was suggestive of GCA, had positive temporal artery biopsy results (9).…”
Section: To the Editormentioning
confidence: 99%